The forgotten trails of the Bokoni : Conserving an Abandoned Heritage Landscape in Mpumalanga by Reviving Historic Patterns of Movement - Prinsloo, Johan Nel (University of Pretoria, 2021)
Mini Dissertation (ML (Prof))--University of Pretoria, 2020.